An update on subtypes of hepatocellular carcinoma: From morphology to molecular - Monika Vyas; Dhanpat Jain (Wolters Kluwer Medknow Publications, 2021)
The morphologic spectrum of hepatocellular carcinoma (HCC) is quite broad. While in about one-third of cases, the neoplasms can be categorized into meaningful subtypes based on morphology, a vast majority of these neoplasms are morphologically heterogeneous. With extensive tumor profiling, data has begun to emerge which can correlate specific morphologic features with underlying molecular signatures. A true morphologic subtype not only has reproducible H & E features, further supported by specific immunohistochemical or molecular signatures, but also has specific clinical implications and prognostic associations. Eight such morphologic subtypes are recognized by the 2019 WHO classification of tumors with a few more additional subtypes described in the literature. The goal of this review is to familiarize the reader with the morphologic subtypes and elaborate on the clinical and molecular associations of these neoplasms.